The Roles of Images in EU Politics. (10th May 2021) - Lynggaard, Kennet
Abstract: The purpose of this article is to advance our understanding of the role of visual discourse in day‐to‐day European Union (EU) politics. The article presents an analytical framework allowing for a fourfold view on the roles of images in politics; namely, images as: (1) emblems underpinning actors' interests, (2) representations of collective meaning‐making, (3) means of domination and (4) ordering devices for including/excluding actors and ideas in politics. The article zooms in on the EU Commission visual discourse and analyses images from three Directorate‐General flagship magazines. The article argues that, the Commission adheres – and increasingly so – to a visual discourse allowing the Commission to set policy agendas and frame policy options, while avoiding creating adversaries among other key actors in EU politics. It also allows for identity‐building, while eschewing further estranging publics sceptical of EU supranationalism and keeping political actors in favour of common EU policies on board.